Women and grassroots leadership - Kaplan, Temma (My University, 1996)
A new generation of women leaders is carrying out an invisible revolution. All over the globe certain women have been asserting collective rights to protect their children against pollution, disease, and homelessness. Not content merely to fight for improvements in the lives of their individual families, many of these women leaders struggle to assure community rights rooted in human need according to an interpretation of democracy that they themselves are developing through their actions. In various resistance movements from the seventies on, women activists have transformed desires to protect their children and their homes into political claims about what democracy should mean. For these leaders and the movements in which they participate, democracy entails human rights based on a standard they themselves define. The implicit theory of human rights they promote seeks to make community health a corollary of justice, deriving its power from common sense notions of human need rather than codified laws.
African Studies Seminar series. Paper presented 29 July 1996
Keywords: Women. Political activity. United States; Women and democracy. United States